Aktivitas Ekstrak Daun Teh Hijau (Camellia sinensis (L.) Kuntze) Terhadap Bakteri Streptococcus Mutans Dengan Perbedaan Tingkat Kepolaran Pelarut - Rosalina L.S, Fazrisa; Septiani Agustien, Gina; Rizkuloh, Lina Rahmawati (Universitas Bhakti Kencana, 2025)
Oral health is an important aspect that should be considered as part of broader efforts to improve overall health (Ministry of Health of the Republic of Indonesia, 2019). The prevalence of dental issues has increased from 23.3% to 25.9%. One of the major dental problems in Indonesia is dental caries, which is classified as a disease. Research on the activity of green tea leaf extract (Camellia sinensis (L.) Kuntze) from various solvent polarity levels has been conducted. This study aims to identify the activity of green tea leaf extract and its inhibitory effect on the growth of Streptococcus mutans bacteria. The extraction method used in this study was maceration with three solvent polarities: n-hexane (non-polar), ethyl acetate (semi-polar), and ethanol (polar). The extract's ability to inhibit bacteria was tested using the disc diffusion method. The results showed that 96% ethanol at a concentration of 10% had an inhibition zone of 11.02 mm (strong category).